Predictors of Authorised and Unauthorised Absence of Secondary School Pupils in Scotland - Treanor, Morag; Behrens, Silvia; Troncoso, Patricio; Williamson, Lee; Lee-Shield, Bethany; MacIntyre, Cecilia (International Journal of Population Data Science, 2025)
Our paper examines the factors associated with increased absenteeism in Scottish secondary schools, considering the phenomenon of persistent absenteeism (defined as an absence rate of 10% or higher) and differentiating between authorised and unauthorised absences. We aim to identify singular and accumulative effects of multiple disadvantages and inequalities on school attendance. We draw on educational data from the Scottish Government, including the Pupil Census, on attendance, absence and exclusions, linked to the Census and health records, from 2007/08-2018/19. The analysis focuses on pupils in secondary school and accounts for variations of random effects in absence data attributable to local authorities and schools. To predict probabilities for pupils being persistently absent, we use multilevel mixed-effects logistic regression. To model authorised and unauthorised absence, we employ mixed-effects negative binomial models. Key variables of interest include eligibility for free school meals (FSM), care experience, additional support needs (ASN), mental health and health conditions of children and parents. Our results strongly suggest that there is a link between low income, using free school meal eligibility as a proxy, and educational absence. Pupils who have been eligible for free school meals at least once throughout their educational trajectory are twice as likely to be persistently absent from school than their peers who had never been eligible. The probability of being absent for 10% or more of a school year has been increasing over the past years. Increases in authorised absence are associated with FSM eligibility, specific ASN, and health factors. Increases in unauthorised absence are strongly influenced by FSM eligibility, care experience, most ASN, and mental health. In forthcoming analysis, we explore how trajectories of absence are related to exclusions from school. The findings provide us with a detailed picture of adverse influences on secondary school pupils’ attendance. The differences of factors associated with authorised and unauthorised absence underline the importance of recognising these patterns on a structural level to address school absenteeism.